(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
In a haugh adjacent to the Water of Eye, labourers who were cutting peat found two cooking vessels buried about 15 inches below the surface. One appeared to be well-used, with evidence of fire marks on it. The other had been worn thin at one point and reinforced. The two vessels were inverted one on the other, and between them were found a bronze Roman patella, a large iron chain, a bronze ornament, two knives, two gouges, a tankard, and a mouthpiece for a musical instrument.